The missing link: Toward an assessment of innovation capacity in health care organizations - Pieter J. Kievit; Jeanette Oomes; Marianne Schoorl; Piet Bartels (International Journal of Quality Innovation, 2018)
The health care sector shows a disjunction between the well-understood necessity for change and the capacity to realize it. Conventional management strategies and traditional means of influencing professionals often fail to deliver projected outcomes. We address this issue from a different angle. An organization's capacity for change is determined by the combination of power distribution, value system and change readiness, which should be analyzed not as formal qualities but as aspects of the organization as a social system, disclosing a reality beneath the surface of mission statements, quality policy and management models. We describe a method to analyse the identity of an organization as a social system with respect to its innovation potential. This identity shows in the rules of discourse determining what is valid communication and which are the sources of impact of arguments in a communicative interaction leading to decisions. We present two case studies in which groups of physicians argue in favor of respectively against the availability of physician-assisted death (PAD) for terminal patients.
Keywords: 650; Health care innovation; Innovation profile; Quality management; Systems theory; Patient participation; Shared decision making; Discourse analysis